The four P's marketing strategies - Pearce, Mark; Video Education Australasia (Bendigo, Vic. : Video Education Australasia, 2009)
This program focuses on how three different business effectively apply marketing strategies, focusing on the 4P's of marketing; product, place, price and promotion. Analysed are common aspects that relate to all markets, and how they come together forming part of the marketing mix
Executive producer, Simon Garner
Voice over: Michael Wahr
DVD format
Keywords: Marketing -- Study and teaching; Place marketing -- Study and teaching; Advertising -- Study and teaching; Product life cycle -- Study and teaching; Pricing -- Study and teaching